Teaching Approaches to Enhance Social Interaction for Student with Hearing-Impaired at Higher Education Level in Lahore - Arif, Amna; Rani, Saima; Siddique, Quba (Annals of Human and Social Sciences, 2024)
The present study intended to explore the importance of classroom social participation, explain the challenges teachers and students face while promoting social participation in classroom, describing the strategies teachers use to enhance the social participation, find out the challenges teachers face while facilitating social participation and explain the teachers’ management of the challenges in promoting social participation. Previous studies have focused on students' experiences, but teachers' use of social inclusion techniques was less studied. This study used phenomenological research design. A sample of 10 teachers of students with hearing impairment was recruited using a purposive sampling technique. The researcher collected the data by physical visits to each district using an interview protocol. The data was analyzed by using thematic analysis. It was revealed that social participation improves social abilities, enhances social resilience, empowers confidence, enhances classroom engagement, and improves communication. Students‟ challenges were related to communication, variation in sign language and low levels of confidence. Teachers use audio translators, assigning group work to enhance the sense of teamwork, and educational Trips. Teachers‟ challenges included the students‟ behavioral issues, their introverted personality type and time management. Teachers reported that they overcome the challenges they face by involving the students in peer tutoring activities, designing interactive games and collaborative teaching. Future researcher should select sample from wider population and include people with different types of special needs in their sample.